Fish Composition at Upstream and Downstream of Batang Ai Hydroelectric Reservoir, Sri Aman, Sarawak - Nadhirah, binti Ahmad (Universiti Malaysia Sarawak (UNIMAS), 2014)
This study was conducted to document the fish composition, diversity and abundance as well as selected water quality parameters at upstream of Batang Ai and Engkari River, and downstream of Batang Ai Reservoir. For each station, selected water quality parameters were recorded and fish was collected using monofilament gill nets of different mesh sizes, three-layered net, cast net and electro-shocker device powered by 1000-watt portable AC generator. A total of 637 individuals of fish were caught from all stations with Cyprinidae as the dominant fish family (86.2%), followed by the family Balitoridae (3.8%), Bagridae (2.4%), Eleotridae (2.4%), Gobiidae (1.1%), Helostomatidae (1.1%), Plotosidae (0.9%), Notopteridae (0.6%), Mastacembelidae (0.5%), Channidae (0.3%), Clariidae (0.3%), Osphronemidae (0.3%) and Cichlidae (0.2%). Fish in the upstream of Batang Ai and Engkari River were dominated by Rasbora caudimaculata with 168 individuals caught, followed by Osteochilus enneaporos with 42 individuals and Rasbora semilineata with 36 individuals, while fish in downstream of Batang Ai reservoir was dominated by Cyclocheilichthys apogon with 108 individuals caught, followed by Hampala macrolepidota with 26 individuals and Cyclocheilichthys armatus with 23 individuals. The upstream of Batang Ai area has better water quality and higher species composition, diversity (2.45) and abundance compared to fish diversity in the upstream of Engkari River (1.49) and the downstream area (1.91).